2018
DOI: 10.1021/acschemneuro.8b00354
|View full text |Cite
|
Sign up to set email alerts
|

Stimulations of the Culture Medium of Activated Microglia and TNF-Alpha on a Scrapie-Infected Cell Line Decrease the Cell Viability and Induce Marked Necroptosis That Also Occurs in the Brains from the Patients of Human Prion Diseases

Abstract: Activation of microglia and increased expression of TNF-α are frequently observed in the brains of human and animal prion diseases. As an important cytokine, TNF-α participates in not only pro-inflammatory responses but also in cellular communication, cell differentiation, and cell death. However, the role of TNF-α in the pathogenesis of prion disease remains ambiguous. In this study, the activities of a scrapie-infected cell line SMB-S15 and its normal partner SMB-PS exposed to the supernatant of a LPS-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…According to the report by Ma et al [19] with some modification, the VSMCs were divided into 6 groups, cultured in 12-well plates with 1 ml DMEM with 10% FBS and 100 U/ml penicillin-streptomycin, and treated as follows: group 1 received 10% BV2 culture supernatant (treated with LPS) and 10 mM β-glycerophosphate (Sigma, Poole, Dorset, UK); group 2 received 10% BV2 culture supernatant (treated with LPS), which was incubated with 7 μl rabbit anti-mouse TNFα antibody (BOSTER Biological Technology Co. Ltd., China) at 4°C for 12 h and 10 mM β-glycerophosphate; group 3 received 10 mM βglycerophosphate and 10 ng/ml mouse TNFα (BOSTER Biological Technology Co. ltd., China); group 4 received 10 ng/ml mouse TNFα; group 5 received 10 mM βglycerophosphate; and group 6 received equal volume of PBS. The VSMCs of all groups were cultured at 37°C and 5% CO 2 for 5 days, and the culture supernatants were replaced at day 3.…”
Section: Induction Of Vsmc Calcificationmentioning
confidence: 99%
“…According to the report by Ma et al [19] with some modification, the VSMCs were divided into 6 groups, cultured in 12-well plates with 1 ml DMEM with 10% FBS and 100 U/ml penicillin-streptomycin, and treated as follows: group 1 received 10% BV2 culture supernatant (treated with LPS) and 10 mM β-glycerophosphate (Sigma, Poole, Dorset, UK); group 2 received 10% BV2 culture supernatant (treated with LPS), which was incubated with 7 μl rabbit anti-mouse TNFα antibody (BOSTER Biological Technology Co. Ltd., China) at 4°C for 12 h and 10 mM β-glycerophosphate; group 3 received 10 mM βglycerophosphate and 10 ng/ml mouse TNFα (BOSTER Biological Technology Co. ltd., China); group 4 received 10 ng/ml mouse TNFα; group 5 received 10 mM βglycerophosphate; and group 6 received equal volume of PBS. The VSMCs of all groups were cultured at 37°C and 5% CO 2 for 5 days, and the culture supernatants were replaced at day 3.…”
Section: Induction Of Vsmc Calcificationmentioning
confidence: 99%
“…However, we have also identified that lots of abnormally regulated brain proteins in prion-infected animals do not significantly change in SMB-S15 cells or change in opposite direction, such as αΒ-crystalline, brain-derived neurotrophic factor (BDNF) and the relevant factors (TrkB, p-TrkB, GRB2 and p57NTR), metalloproteinase (ADAM10), glucose transporter 3 (GLUT3), and Polo-like kinases 3 (PLK3) ( Wang et al, 2013 ; Chen et al, 2014 ; Yan et al, 2014 ; Ting-Ting Wang et al, 2016 ; Wang et al, 2017 ). Moreover, majority of the abnormally expressed proteins in SMB-S15 cells can be completely or partially converted by removal of prion replication with resveratrol, but some do not, such as RyR2 and caspase 8 ( Shi et al, 2018 ; Ma et al, 2019 ). We assume that although prion-infected cell lines mimic to some extent the prion infection in vivo , it more reflects a situation that the cells adopt the propagation and accumulation of prions; thus, the protein changing profile in prion-infected cell line may differ with that in the brains of prion-infected animals.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, neuroinflammation induce subsequently pathophysiological effects, either neuroprotective or neurotoxic. Active neuroinflammation responses have been well documented in prion diseases, represented by activation of microglia, complement system and numerous inflammatory cytokines [26][27][28][29][30][31]. IP10 is mainly secreted by microglia in CNS after LPS stimulation [32].…”
Section: Discussionmentioning
confidence: 99%